2006
DOI: 10.4269/ajtmh.2006.74.444
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Detection of Rickettsia Felis in Cat Fleas (Ctenocephalides Felis) From Israel

Abstract: The presence of Rickettsia felis, an emerging bacterial pathogen, was investigated in 79 cat flea (Cteno-cephalides felis) pools from Israel (5 to 20 fleas each) by polymerase chain reaction (PCR) and sequencing of 5 different genes. Amplified targets included both metabolic (gltA and fusA) and surface antigen (ompA, ompB, and the 17-kDa antigen) genes. R. felis DNA was detected in 7.6% of the flea pools. Two genotypes similar in their housekeeping gene sequences but markedly different in their surface antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
0
14
0
4
Order By: Relevance
“…In addition, previously demonstrated serologic evidence of spotted fever group rickettsiae infection among residents of Gag Island, in eastern Indonesia (15), could have been due to R. felis. On the basis of data presented here and of recent reports of R. felis in other countries in Asia (2)(3)(4)(5)8,9), healthcare providers in Indonesia should be alerted to the possibility of fleaborne spotted fever among their patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previously demonstrated serologic evidence of spotted fever group rickettsiae infection among residents of Gag Island, in eastern Indonesia (15), could have been due to R. felis. On the basis of data presented here and of recent reports of R. felis in other countries in Asia (2)(3)(4)(5)8,9), healthcare providers in Indonesia should be alerted to the possibility of fleaborne spotted fever among their patients.…”
Section: Discussionmentioning
confidence: 99%
“…The biology of these species is not well known in Korea and may reflect host and/or ectoparasite reproductive seasonal differences. The PCR techniques used in our study for detection of R. typhi (Webb et al, 1990) have been used for identifying Rickettsia pathogens in the cat flea, Ctenocephalides felis, from various countries throughout the world, including Cyprus (Psaroulaki et al, 2006), Mexico (Zavala-Castro et al, 2005), Peru (Blair et al, 2004), Afghanistan (Marie et al, 2006), USA (Reeves et al, 2005), and Israel (Bauer et al, 2006). Positive pools found in this study were observed from fleas taken only from A. agrarius that were negative by IFA for R. typhi.…”
Section: Discussionmentioning
confidence: 99%
“…IG-1, TwKM01, TwKM02, and TwKM03) were detected recently in Ixodes granulatus, Rhipicephalus haemaphysaloides, Leptotrombidium deliense, and Mesostigmata vectors in Taiwan (Tsai et al 2008b, Tsui et al 2007). Flea-borne rickettsioses caused by Rickettsia felis were recently designated as a transitional group and have been discovered in vector fleas in many Asian countries including Thailand, Afghanistan, and Israel (Bauer et al 2006, Gillespie et al 2007, Marie et al 2006, Parola et al 2003. R. felis is primarily transmitted transovarially by the cat flea, Ctenocephalides felis (Siphonaptera: Pulicidae), and human infections with R. felis have clinical symptoms similar to those of murine typhus (Azad et al 1997, Parola et al 2003.…”
Section: Introductionmentioning
confidence: 97%